1994
DOI: 10.1177/107110079401500406
|View full text |Cite
|
Sign up to set email alerts
|

Gait Analysis and Dynamic Foot Pressure in the Assessment of Treated Clubfoot

Abstract: Gait analysis and dynamic foot pressure were used in a follow-up study of 42 children with idiopathic clubfeet. Mean age at follow-up was 9 years (range 4-15 years). Twenty-four of the 62 clubfeet were treated conservatively and 38 had at least one operative intervention. Gait analysis showed that the vertical and posterior ground forces were significantly lower from the clubfoot compared with the normal foot. Dynamic foot pressure demonstrated a significant shift of the center of pressure to the lateral side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 9 publications
5
29
0
1
Order By: Relevance
“…Angular parameters were also different in CF children with less plantar exion range of motion for unilateral CF group, on both sides, compared with control group. ese ndings are similar W and B 6 and H et al 7 . ese imbalances are related to constrains in m. triceps surae associated with surgical procedures and residual deformities after treatment.…”
supporting
confidence: 70%
See 3 more Smart Citations
“…Angular parameters were also different in CF children with less plantar exion range of motion for unilateral CF group, on both sides, compared with control group. ese ndings are similar W and B 6 and H et al 7 . ese imbalances are related to constrains in m. triceps surae associated with surgical procedures and residual deformities after treatment.…”
supporting
confidence: 70%
“…e weakness of muscle stabilizers or decreased amplitude in ankle angle (normally found in CF children) could contribute to these angular alterations and could justify the decrease in vertical GRF in midstance phase found in the unilateral CF group. e nal gait stance phase, propulsion de ciencies found in CF groups are similar to W and B 6 , T et al 3 and F et al…”
supporting
confidence: 52%
See 2 more Smart Citations
“…This study demonstrated that both treatments resulted in residual varus as well, with the operative group having a significantly greater varus. Similarly, Widhe and Berggren [24] reported a significant shift in the pressure from the center to the lateral side of the foot in children with clubfoot who had been treated conservatively. Furthermore, in a 2009 study, Sinclair et al [47] reported that, compared to an unaffected foot, a surgically treated clubfoot had a reduced peak pressure over the medial hindfoot and forefoot.…”
Section: Coronal Planementioning
confidence: 99%